Open Source Evaluatology: An evaluation framework and methodology for open source ecosystems based on evaluatology - Fanyu Han; Shengyu Zhao; Wei Wang; Aoying Zhou; Weining Qian; Xuan Zhou; Jiaheng Peng; Lan You; Yang Chen; Xiaoya Xia; Yenan Tang; Liyun Yang; et al. (BenchCouncil Transactions on Benchmarks, Standards and Evaluations)
The open-source ecosystem, as an important component of the modern software industry, has increasingly attracted attention from both academia and industry regarding its evaluation. However, current open-source evaluation methods face several issues, such as inconsistent evaluation standards, lack of theoretical support in the evaluation process, and poor comparability of evaluation results. Guided by the foundational theories of evaluatology, this paper proposes a new interdisciplinary research field, Open Source Evaluatology, and constructs an evaluation theoretical framework and methodology for open-source ecosystems. The main contributions of this paper include: (1) Based on the five axioms of evaluation theory, a theoretical system for Open Source Evaluatology is developed, and the basic concepts, evaluation dimensions, and evaluation standards for the open-source ecosystem are proposed; (2) An evaluation conditions (EC) framework is designed, encompassing five levels: problem definition, task instances, algorithm mechanisms, implementation examples, and supporting systems. A combined evaluation model (EM) based on statistical metrics and network metrics is also introduced; (3) Experimental validation using the GitHub dataset shows that the proposed evaluation framework effectively assesses various features of open-source projects, developers, and communities, and has been verified in multiple practical application scenarios. The research demonstrates that Open Source Evaluatology provides a standardized theoretical guide and methodological support for open-source ecosystem evaluation, which can be widely applied in various scenarios, such as open-source project selection, developer evaluation, and community management, and plays a significant role in promoting the healthy and sustainable development of open-source ecosystems.